Effects of Helmholtz coil magnetic fields on microstructure and mechanical properties for sand-cast A201 Al-Cu alloy. (2nd December 2020) - Wang, Cheng-Shun; Lin, Shih-Chao; Lin, Tsung-Ying; Wang, Jian-Yih; Muhfidin, Rivan; Yu, Ing-Song
Abstract: In this report, the effects of magnetic fields by using Helmholtz coils on the microstructures and mechanical properties of sand-casting Al-Cu alloys were firstly investigated. Due to the magnetic field stirring effect during the solidification process, the average grain size of sand-casting A201 ingots decreased, and the uniformity of α -Al grain increased. The grain refinement by the magnetic fields equipped with Helmholtz coils enhanced the mechanical properties of sand-casting A201 ingots, including hardness, yield strength, ultimate tensile strength and elongation. Meanwhile, according to the characterization of x-ray diffraction, preferred orientation (111) planes of α -Al phase was observed as the increase of the magnetic field. The magnetic field of Helmholtz coils provided the Lorenz force to agitate the melt during the solidification of sand-casting Al-Cu ingots, which had influence on the migration of solid-liquid interface and the rotation of the single-crystal nucleus. In summary, an easy and low-cost technique was proposed to improve the mechanical properties of sand-casting A201 alloys.